Ultrasound assisted lipase catalyzed synthesis of poly-6-hydroxyhexanoate - Gumel, A.M.; Annuar, M.S.M.; Heidelberg, T.; Chisti, Y. (Elsevier, 2012)
Ultrasonic irradiation greatly improved the Candida antarctica lipase B mediated ring opening polymerization of e-caprolactone to poly-6-hydroxyhexanoate in the ionic liquid 1-ethyl-3-methylimidazolium tetraflouroborate. Compared to the conventional nonsonicated reaction, sonication improved the monomer conversion by 63% and afforded a polymer product of a narrower molecular weight distribution and a higher degree of crystallinity. Under sonication, the polydispersity index of the product was 1.44 compared to a value of 2.55 for the product of the conventional reaction. With sonication, nearly 75% of the monomer was converted to product, but the conversion was only 16% for the reaction carried out conventionally. Compared to conventional operation, sonication enhanced the rate of polymer propagation by >2-fold and the turnover number of the lipase by >3-fold.